1978
DOI: 10.1017/s0021859600048711
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of utilization of food energy by growing pigs

Abstract: SUMMARYThe efficiency of utilization of the energy of the food by growing pigs of the Large White breed was measured. Ten diets had a digestible energy varying from 75·3 ± 0·91 to 85·7 + 0·81% and a metabolizable energy from 72·3± ·92 to 83·4±0·64% of the gross energy. Net energy was 85·2±3·20% of the metabolizable energy (ME).Regression calculations resulted in the following estimates: a maintenance requirement of 151 kcal ME for growing pigs weighing 9–58 kg and efficiencies of 66·7 and 100% for the utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Estimates of bp ranged from 7.43 kcal/g (Burlacu et al, 1973) to 15.96 kcal/g (Kielanowski and Kotarbinska, 1970). The range for estimates of bF was 9.5 kcal/g (Burlacu et al, 1976) to 16.16 kcal/g (Sharma and Young, 1970). There was more variation between experiments for estimates of bp than for estimates of b F and Kielanowski (1965) has discussed possible explanations for this variability.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of bp ranged from 7.43 kcal/g (Burlacu et al, 1973) to 15.96 kcal/g (Kielanowski and Kotarbinska, 1970). The range for estimates of bF was 9.5 kcal/g (Burlacu et al, 1976) to 16.16 kcal/g (Sharma and Young, 1970). There was more variation between experiments for estimates of bp than for estimates of b F and Kielanowski (1965) has discussed possible explanations for this variability.…”
Section: Resultsmentioning
confidence: 99%
“…Holmes et al (1980) found energy diges tibil ity figures for ma ize/barley rations to be 82% -84% . One might expect a lowe r di gestibility for the present ration wh ich inc luded a higher proportion of barley (Burlacu et al , 1978 ;Mo r gan et al , 1975�) . Digestibility of nitrogen (77%) was close to values given by Holmes et al (1980) of 76% and 80% .…”
Section: 5mentioning
confidence: 91%
“…O consumo de EM diário médio no mesmo período foi de 8232 kcal/dia (3250 kcal EM/kg da dieta) para os machos castrados alimentados AV e 7673 kcal/dia para os que iniciaram a RA aos 60 kg de peso vivo, o que corresponde a 3,39 e 3,16 vezes a necessidade de mantença, respectivamente. Dependendo do nível de restrição imposto e da faixa de peso em que a restrição é aplicada, a retenção de energia pode ser reduzida, como foi observado por BURLACU et al (1978), com restrição de 20% do consumo à vontade em leitões em crescimento.…”
Section: Resultsunclassified